Analisis Kemampuan Komunikasi Matematika Siswa Ditinjau dari Motivasi Berprestasi - Aspriyani, Riski; Hartono, Bryan Pudji (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The achievement motivation that exists in students needs to be stimulated so as to provide better changes for their learning outcomes. One of the results of learning mathematics can be seen is mathematical communication ability in solving a given mathematical problem. For this reason, this quantitative descriptive research was conductide with aimed to know the differences in students' mathematical communication ability reviewed high, medium, and low achievement motivation. The data was taken using essay test and a questionnaire to 67 students as respondents at SMA Negeri 1 Purbalingga in 2021. The sampling used purposive sampling technique. Data analysis used descriptive and inferential statistics. In inferential statistics, the One Way ANOVA test with alpha 5% was used and continued using the Scheffe method. ANOVA test prerequisites for Normality test analysis using Kolmogorov Smirnov and Homogeneity test. The result are H0 is rejected with a significance value 0.002 < 0.05 or Fh=7,159 > F 0,05;2;64= 3,23 . It means that there are differences in mathematical communication reviewed achievement motivation. Then does post ANOVA test with the result are students who have high achievement motivation better mathematical communication than students with medium and low. Meanwhile, students who have medium and low achievement motivation have the same good mathematical communication ability.